1990
DOI: 10.1530/jrf.0.0880593
|View full text |Cite
|
Sign up to set email alerts
|

Resumption of gonadotrophin release during the post-partum period in suckling and non-suckling ewes

Abstract: Summary. The post-partum secretion of LH, FSH and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…In ewes, FSH secretion followed a quite clear wave-like pattern from the day after lambing that suggested a 4-6-day rhythm [37]. These findings are concomitant with earlier findings in cyclic goats [38] and indicated that the follicular waves occur regularly under conditions of basal LH and FSH during the postpartum period in the goat.…”
Section: Discussionsupporting
confidence: 86%
“…In ewes, FSH secretion followed a quite clear wave-like pattern from the day after lambing that suggested a 4-6-day rhythm [37]. These findings are concomitant with earlier findings in cyclic goats [38] and indicated that the follicular waves occur regularly under conditions of basal LH and FSH during the postpartum period in the goat.…”
Section: Discussionsupporting
confidence: 86%
“…However, in our study, the elevated PRL levels did not decrease rapidly as in cows [4][5][6][7][8], and the elevated levels gradually decreased with time after parturition. These differences are thought to be derived from the stimulation of suckling by kids, since the suckling stimulates a PRL release in goats [6] and sheep [39]. In our experiment, the nursing goats were kept with their kids and allowed to be suckled freely throughout the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been suggested that high concentrations of circulating progesterone and estradiol in pregnant ewes inhibited GnRH secretion in the hypothalamus [19]. However, ewes have been known to show recovery in the pulsatile secretion of GnRH within 3 weeks after lambing followed by the increase in the estradiol receptor in the hypothalamus and adenohypophysis when she lambed in the early breeding season [9,20]. These physiological changes in postpartum ewes lead to the resumption of subsequent estrous cyclicity.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in the mid-latitude regions have indicated that the resumption of the breeding season for non-lactating ewes administered melatonin occurred earlier than that in control ewes. On the other hand, it has been suggested that length of postpartum anestrus was affected by the lambing season, lactation and nutrition [7][8][9]. If early postpartum ewes…”
mentioning
confidence: 99%